Waste heat harness in a thermal energy system using TEGs, and SCO2 brayton cycle driven by renewable sources for electricity and liquid hydrogen Production: Thermo-Economic optimization using ANNs - Amr S. Abouzied; Sarminah Samad; Pradeep Kumar Singh; Ahmed H. Janabi; Mohamed Shaban; Asma Ahmed A. Mohammed; Shoira Formanova; H. Elhosiny Ali; Samah G. Babiker; Abdulrahman M. Alansari (Case Studies in Thermal Engineering)
This research introduces an innovative thermal energy system that combines solar and wind energy to produce electricity, generate hydrogen, and facilitate liquefaction. This system includes a parabolic trough solar collector (PTSC) that heats nitrate salts, transferring the thermal energy to a supercritical carbon dioxide Brayton cycle (SCO2-BC). Furthermore, thermoelectric generators (TEG) are integrated to capture energy from waste heat sources. Additionally, this study breaks new ground by incorporating solar and wind power with a supercritical CO2 cycle alongside hydrogen liquefaction, a field that is still relatively uncharted. A detailed techno-economic and environmental model is utilized to assess the system's performance, concentrating on critical indicators such as second law efficiency, total cost rate, hydrogen production rate, net power output, levelized costs, and the rate of CO2 emission reduction. Following this, an optimization process is carried out using a genetic algorithm to investigate two different scenarios. Finally, the LINMAP method is applied to identify optimal solutions for each scenario. The study reveals that the system generated a grid power output of 461.2 kW and produced 8.3 kg of liquid hydrogen per hour. The overall cost of operation was established at 103.8 $/h with an exergy efficiency of 16.2 %. Further refinements resulted in values of 19.33 % for second-law efficiency, 124.80 $/h for cost rate, and 1021.64 kW for grid power.